TELAAH MANTIK DALAM UNGKAPAN KONTROVERSIAL ROCKY GERUNG “Kitab Suci itu Fiksi” - Sri Sitipuji Astuti; Nandya Putriani Asharina; Indra Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This article aims to describe Roky Gerung's phrase in a fictional statement of the scriptures presented in a television show. The method used in this research is descriptive qualitative. The object of this research is a roky revelation in an electronic event. The phrase Rocky Gerung when viewed in the level of semantic science in this case Mantik science, the theory used is Mantik. Mantik is the science of logic. This mantle emphasizes the meaning of words in terms of logic. The results of the analysis show that this statement uses a pattern if then. Thus, Rocky Gerung's statement is not wrong because if it justifies his statement, the conclusion to the scripture is fiction justified. However, if one does not justify the preceding statement and conclude that the scripture is fiction is certainly not justified.